Are music listening strategies associated with reduced food consumption following negative mood inductions; a series of three exploratory experimental studies. (1st May 2022) - van den Tol, Annemieke J.M.; Coulthard, Helen; Lang, Victoria; Wallis, Deborah J.
Abstract: Emotions play an important role in overeating, yet there is little research looking at practical strategies to reduce overeating in response to a negative mood. In three different experimental studies, we tested if exposure to music can reduce food consumption in a negative mood. Female undergraduates ( N  = 120–121 in each study) completed a measure of emotional eating and reported baseline hunger. Mood ratings were taken at baseline, post-mood induction and post-eating. All participants were given a mood induction (sadness for study 1, stress for studies 2 and 3) and allocated to one of three music conditions (self-chosen in study 3) or a silent (control) condition. Music was selected from three pieces reported by each participant as being listened to regularly when experiencing the negative mood being examined (sadness or stress) in order to provide solace (comforting music), diversion (distracting positive music), or discharge (angry and/or sad music). Participants were provided with several snack foods to consume whilst completing a mock taste test and intake (in grams) was compared between conditions. In study 1 participants in the music for discharge condition consumed less than those in the control condition. Moreover, participants with high levels of self-reported EE ate more crisps in the control than in the distraction condition. In study 2 participants in the solace condition consumed less than those in the control and discharge conditions. In study 3 most participants chose music for diversion; this did not, however, lead to lower consumption, despite a reduction in reported stress. Overall, the results of these studies indicate that listening to certain types of music might reduce emotion-related eating after controlling for hunger using a standardized pre-session snack. Highlights: Music listening might help to prevent overeating when experiencing negative emotions. Music for discharge (study 1) in a sad mood results in lower food intake. Music for diversion (study 1) results in less food intake for those with high levels of EE. Music for solace (study 2) under stress results in lower food intake. Self-selected music for diversion (study 3) reduced stress, not intake. Need to examine the potential for music to reduce emotional eating in the real world.